Cross and cosmos : a theology of difficult glory - Caputo, John D. (Indiana series in the philosophy of religion., 2019)
"John D. Caputo stretches his project as a radical theologian to new limits in this groundbreaking book. Mapping out his summative theological position, he identifies with Martin Luther to take on notions of the hidden god, the theology of the cross, confessional theology, and natural theology. Caputo also confronts the dark side of the cross with its correlation to lynching and racial and sexual discrimination. Caputo is clear that he is not writing as any kind of orthodox Lutheran but is instead engaging with a radical view of theology, cosmology, and poetics of the cross. Readers will recognize Caputo's signature themes-hermeneutics, deconstruction, weakness, and the call-as well as his unique voice as he writes about moral life and our strivings for joy against contemporary society and politics"--